INTERVENSI PEMERINTAH TERHADAP MEKANISME PASAR DALAM PERSPEKTIF EKONOMI ISLAM - Rahman, Abd; Zakiyah, Makhsusi; Anwar, Khoirul (Iltizam : Jurnal Ekonomi dan Keuangan Islam, 2025)
This article explores government intervention in market mechanisms from an Islamic economic perspective. In free market theory, the forces of demand and supply are believed to naturally create price equilibrium. However, in practice, market distortions often occur—such as monopolies, speculation, fraud in measurement, and domination by certain economic actors—resulting in social and economic inequalities that necessitate active government involvement. In Islamic economics, the market is not an entirely free entity but a system that must adhere to principles of justice, honesty, and balance. Hence, government intervention is not viewed as authoritarian but as a moral and religious obligation to protect public welfare (maslahah ‘ammah). This study employs a qualitative library research approach, analyzing both classical and contemporary Islamic economic literature, including the thoughts of al-Ghazali, Ibn Taymiyyah, and al-Mawardi. The findings reveal that government intervention is permissible in Islam when it aims to uphold Sharia values. Forms of intervention include market supervision through the hisbah institution, price regulation (tas’ir) during economic crises, and control over measuring instruments. In conclusion, government intervention in markets is an integral part of the Islamic economic system, aiming to establish justice and protect society. This perspective distinguishes Islamic economics from capitalism, which overly emphasizes individual freedom. Intervention in Islam is not about restriction but about guiding the market to remain ethical, fair, and compliant with Sharia principles.